Can we detect Li K X‐ray in lithium compounds using energy dispersive spectroscopy?. Issue 6 (3rd February 2016) - Hovington, Pierre; Timoshevskii, Vladimir; Burgess, Simon; Demers, Hendrix; Statham, Peter; Gauvin, Raynald; Zaghib, Karim
Summary: Lithium is the key element for the development of battery and new technology and the development of an analytical technique to spatially and quantitatively resolve this element is of key importance. Detection of Li K in pure metallic lithium is now possible in the Scanning Electron Microscope (SEM) with newly designed Energy Dispersive Spectroscopy (EDS). However, this work is clearly showing, for the first time using EDS, the detection of Li K in several binary lithium compounds (LiH, Li3 N, Li2 S, LiF and LiCl). Experimental Li K X‐rays intensity is compared with a specially modified Monte Carlo simulation program showing discrepancies between theoretical and experimental Li K measurements. The effect of chemical bounding on the X‐rays emission using density functional theory with the all‐electron linearized augmented plane wave is showing that the emission of Li K from the binary compounds studied should be, at least, 12 times lower than in metallic Li. SCANNING 38:571–578, 2016. © 2016 Wiley Periodicals, Inc.